If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 16 = 32 Reorder the terms: 16 + m = 32 Solving 16 + m = 32 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + m = 32 + -16 Combine like terms: 16 + -16 = 0 0 + m = 32 + -16 m = 32 + -16 Combine like terms: 32 + -16 = 16 m = 16 Simplifying m = 16
| (24b+14d-10)= | | y/3-4=27 | | 31=7+8x | | p(x)=2x-a^2 | | 8x-9y-3xy-2y+7xy= | | 35-p=12 | | -4(-5t-1+2n)= | | 18-y=15 | | 5x+3x=108 | | 42+a=15 | | 15-n=2 | | 45+1=x | | y-12=22 | | 13(x-9)=15 | | (-20)(4/5) | | 23+p=50 | | 6a^2+30b^2-18b^3a^3= | | 4c+5=6c+1 | | (8x-9x-4)-(4x+3)=4+16 | | -8x+8=16 | | 1/6y=-10 | | x/7=-3/8 | | x+23=67 | | x^2+2x+11=-90 | | Z=9+y | | 9-3(x+7)=4 | | 6d=10+4d | | b^8=96 | | 3x-(-5)=2x-(-6) | | 4a+5=5+2a | | (2+4)*(8-9)= | | 5r-14-14r+9= |